Pendidikan Etika dan Perkembangan Moral Mahasiswa Akuntansi - Laily, Nujmatul; Anantika, Nova Rifinda (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 13 No 1 (2018)DO - 10.24843/JIAB.2018.v13.i01.p02, 2018)
The purpose of this research was to comprehend ethical education differences among level 1 (pre-conventional), level 2 (conventional), and level 3 (post-conventional) toward moral development steps of accountancy students. This research is quantitative research using survey which is held in X University in Malang. The sampleof this research are 176 accountancy students. Sampling method used proportional random sampling technique in choosing the responden.The instrumentof this research is questionnaire related to ethical education or ethical courses and moral development questionnaireusing defining issues test. The results showed that ethical education differ among level 1 (pre-conventional), level 2 (conventional), and level 3 (post-conventional) of accountancy students. Keywords: Moral development, ethics education, accounting